Dynamics and function of the GET system microbial community: insights into the role of the genus Bacillus in biogas production - Chen, Shaohua; Murano, Hirotatsu; Matsushita, Mio; Jindo, Sadanari; Hirano, Tatsuya; Tamura, Hiroto (Frontiers in Microbiology, 2026)
IntroductionTo contribute to a sustainable society, we have established a novel technology for self-sufficient, renewable energy production called the GET system. This system produces approximately 300 liters of biogas from 1 kilogram of untreated rice straw in rice paddy fields while simultaneously reducing methane emissions from those paddies. A key feature of the GET system is that 2nd addition of rice straw, made 2 months later, significantly increased biogas production compared to the initial addition. However, no volatile fatty acids (VFAs)—key substrates for methanogens—were detected after 2nd addition of rice straw.MethodsTo understand this phenomenon, the microbial community in the GET system at various time points was analyzed using next-generation sequencing (NGS) and real-time quantitative PCR (RT-PCR).ResultsVolatile fatty acids (VFAs), particularly acetic acid, are important substrates and indicators for methane production. However, in this study, VFAs, including acetate, were not detected after 2nd addition of rice straw, which significantly increased biogas production. In the analysis of microbial community structure, although bacteria from Clostridium and methanogenic archaea are often considered to play a dominant role in anaerobic cellulolytic fermentation and methanogenesis, respectively, the GET system was dominated by Bacillus, which had an average abundance of 23.8%. This abundance increased fourfold after 2nd addition of rice straw, mainly due to the increased presence of B. fumarioli under strict anaerobic condition, which has been recently transferred into the genus Neobacillus (Patel and Gupta, 2020). However, the average abundance of Methanosaeta and Clostridium accounted for 3.7 and 7.1% of the total, respectively, with no significant changes in abundance throughout the experimental period.DiscussionThe synchronization of the increase in B. fumarioli abundance with the increase in biogas production in the GET system indicated that B. fumarioli plays a key role in maintaining a perfect balance with the methanogenic archaea Methanosaeta by decomposing rice straw, subsequently producing VFA, and ultimately generating acetate, which serves as a substrate for methane production.This study provides the first functional insight into the role of B. fumarioli in efficient methane production under strictly anaerobic conditions.